A RIEMANN-LEBESGUE LEMMA FOR FOURIER-JACOBI COEFFICIENTS - Fejzullahu, Bujar Xh. (Matematichki Bilten, 2006)
Riemann-Lebesgue Lemma for Fourier-Jacobi coefficients for the class of functions in \(L^p_{(α,β)}\), \(1-1\), \(α≥-1/2\).For \(f\in L^p_{(α,β)}\), \(1-1/2\), \(β>-1\) Riemann-Lebesgue Lemma is proved.